Application of Diffusion‐Driven Layer‐by‐Layer Assembly for Fabricating Compact Graphene‐Based Supercapacitors. Issue 16 (6th June 2016) - Zou, Jianli; Zhang, Binbin; Murphy, Elizabeth; Kim, Franklin
Abstract : Squash to retain performance : A diffusion‐driven layer‐by‐layer (dd‐LbL) assembly method is used to prepare films composed of porous graphene oxide scaffold. Even after heavy compression, nanosheets within this scaffold remain in a corrugated state rather than restacking. As a result, when fabricated as supercapacitor electrodes, it becomes possible to compress the device into a compact form without loss in performance.